Torn thread - Isaacs, Anne. (New York : Scholastic Press, 2000)
In an attempt to save his daughter's life, Eva's father sends her from Poland to a labor camp in Czechoslovakia where she and her sister survive the war.
Keywords: World War, 1939-1945 -- Jews -- Juvenile fiction; Holocaust, Jewish (1939-1945) -- Juvenile fiction; World War, 1939-1945 -- Jews -- Fiction; Holocaust, Jewish (1939-1945) -- Fiction; Concentration camps -- Czechoslovakia -- Fiction; Jews -- Europe -- Fiction